City observatory and attractiveness: Case of Laghouat Municipality - BEKKAYE Tahar; ABDELLAOUI Abdelkader (université laghouat, 2016)
The local observatory is one of the observation networks’ levels created by the United Nations in order to monitor the progress of the Global urban observatory (GUO). Such studies are not well known in Algeria, especially for their role of observing the evolution of cities and their urban conditions and trends. In this study we created the city observatory of Laghouat using a Geographic information system (GIS) oriented software while focusing particularly on public facilities, mainly the five sectors of: education, religious affairs, health, culture and sports that we had to find their location in the city and create their location maps. The major obstacle we faced was the unavailability and quality of data that narrowed our analysis later to one field and that is the primary schools field, which also served as a sample application of our analysis using two similar but different methods: the districts division analysis method and the grid analysis method in order to detect the facilities quality of distribution in the city and their impact on their neighborhoods and therefore also the needs of setting up some new facilities. These resulted information helped us in assessing the attractiveness of neighborhoods of the city of Laghouat as well as its attractiveness to immigrants due to its potentials and to the fact of being the capital city of the state of Laghouat. Keywords: Laghouat, City observatory, City attractiveness, Geographic Information System, GIS, Grid analysis method, Public facilities.